Creating Markets in Botswana - A Diamond in the Rough : Toward a New Strategy for Diversification and Private Sector Growth - Country Private Sector Diagnostic - International Finance Corporation (World Bank, Washington, DC, 2022)
Diamonds have been at the center of Botswana’s growth miracle for decade - but the urgency to diversify is stronger than ever. Although Botswana’s economy has undergone transformation over the past decades, the shift has been largely into non-tradable services, with limited gains in employment, income equality, and export diversification. In addition, Botswana’s high vulnerability to climate change, which affects all major sectors of the economy, underscores the need to strengthen Botswana’s response to climate factors as a basis for renewed, sustainable growth. A positive growth outlook and steps taken as part of the Coronavirus disease 2019 (COVID-19) crisis response should give the government new impetus to accelerate reforms. Success in diversifying the economy will depend on the decisive implementation of structural measures to increase private sector participation in nonmineral exports and transformative sectors. The dominant role that the government of Botswana still plays in large parts of the economy, particularly through its footprint as a shareholder in companies in the corporate sector, is a critical constraint that inhibits the entry and success of private sector participants. Gaps in infrastructure, access to finance, and skills are additional key constraints to employment and productivity growth. A coordinated approach to financing entrepreneurship and policies to increase uptake of digital finance can help close the gap. Trade barriers are another key cross-cutting constraint for the private sector, and a greener path for the economy can be unlocked by facilitating improved trade in environmental goods and services (EGS). Three key recommendations for the energy sector are as follows. The first recommendation is the fast tracking of instruments to facilitate investment in energy infrastructure development, including independent power producer (IPP) licensing, and procurement guidelines and processes. The second recommendation is the enhancement of the institutional capacity and governance model of the Botswana Energy Regulatory Authority (BERA). The third recommendation is the development of credit-enhancement and risk-mitigation strategies and supporting instruments to attract and mobilize private sector investment.